Optimising Olympic distance triathlon performance - A biomechanist's perspective. - McLean, B. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
Optimum competition performance is directly related to maximising the average velocity achieved during the race. From a biomechanical perspective maximising velocity involves optimising technique to increase propulsive force production, optimising technique and equipment to minimise the resisting forces that limit velocity and making tactical and technique decisions which conserve energy or limit reductions in velocity. Biomechanics can contribute to optimising ODT performance in these ways. However, given that there is a direct relationship between the ability to train and the competitive performance, and that failure to achieve optimal training loads is primarily due to injury, biomechanics plays a secondary role in optimising competition performance by helping to keep an athlete injury free. Since triathlon is an endurance sport, high numbers of running strides, swimming strokes and pedal cycles are undertaken on a routine basis. A small biomechanical inefficiency can soon lead to injury once many thousands of repetitions are encountered in heavy training. Similarly, anatomical anomalies, technique faults, inappropriate equipment and equipment adjustment can lead to injury without large numbers of repetitions if any of these factors introduce large forces to the body. Specific training techniques can also apply high loads to the body. Inappropriate use of these techniques or incorrect management of their frequency and duration can lead to injury. Biomechanics can play a significant role in preventing injury, which can lead directly to enhanced competition performance.